Digital Marketing Strategy in the Perspective of the Global Value Chain (GVC) of MSME Products: Case Study of Wedang Dayak - Adi Hermawansyah; Sudarmiatin Sudarmiatin; Heri Pratikto (Harmony Management: International Journal of Management Science and Business, 2026)
The Role digital marketing nowadays become part important in today's business strategies implemented by MSMEs, which is enable MSMEs to​​ reach the target market with more broad , measurable , and efficient in global value chain (GVC) context . Digital marketing strategies do not can denied involving various elements, including optimization machine search engine optimization (SEO), marketing through social media, digital advertising, marketing content ,and also email marketing. In buniess process of PT Bungas food Nusatra abalikpapan tahy have product a weadang dayang. In facing such a market dynamic, marketing strategy must capable adapt with current digital trends including Fear of Missing Out (FOMO) approach to create greater urgency and involvement​ tall in a way contextual relation with the value chain that creates consumer new abroad or​ marketing across countries by them. In this case, on of the challege ib export product process. The methods of research here, is survey and looking some literature that related in this subject discussion and research, the conclusion is the With utilise trend this company​ can increase visibility brand , strengthen interaction with customers and encourage conversion sale in a way more effective and This strategy expected can give impact positive to growth business and power competition companies in the digital era in more fluently in global value chain (GVC).